Concept of Rights and Obligations of Husband and Wife in Long Distance Relationship (Case Study in Kuala Terengganu, Terengganu, Malaysia): Konsep Hak Dan Kewajiban Suami Istri Long Distance Relationship (Studi Kasus di Kuala Terengganu, Terengganu, Malaysia) - Binti Mat Razali, Saudah (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
The article writes that the relationship between husband and wife must live in the same house to achieve their rights and obligations as well as the formation of a harmonious marriage. However, in reality, many husbands and wives carry out their obligations remotely because of the need to work for their family's economy. The problems in this article focus on the factors and impacts of husband and wife having long distance relationships in Kuala Terengganu and how long distance husband and wife relationships in Kuala Terengganu fulfill the rights and obligations of their partners. This article was written using empirical legal research methods. Based on the research results, the factors of a long distance husband and wife are firstly, the place of work is far from the village, secondly, the family's economic needs, thirdly, the educational factor at school which has been determined by the government for teachers. The next impact on husband and wife is the impact of long distance couples in Kuala Terengganu. Judging from the positive and negative impacts on long distance couples. The positive impact is that you can maintain a good relationship and feel appreciated in your own way, such as by giving something to your partner. He puts his position in loyalty and trust towards his partner, and can avoid doing bad things. Long distance relationship couples in Kuala Terengganu appreciate their partners more deeply. Judging from the negative impacts of long distance couples in Kuala Terengganu, there are 5 negative impacts, lack of communication, mental health impacts, infidelity, suspicion, and divorce. Next, the pattern of a long distance husband and wife relationship is 5 obligations that are fulfilled, living, maintaining honor, serving the wife, obeying the husband, and hadhanah. Married couples in Kuala Terengganu can fulfill all these obligations, and then each husband and wife can handle them so that their long-distance relationship remains sustainable and happy.